EFFICIENCY OF AN EARLY INTERVENTION WITH PHYSICAL THERAPY ON AN INFANT WITH CONGENITAL TORTICOLLIS (GYMNASIUM, 2017)
Congenital torticollis is a musculoskeletal pathology which is observed at or shortly after birth and is caused by the fibrosis or unilateral shortening of the sternocleidomastoid muscle (SCM). Physical therapy is one of the main intervention methods for torticollis and aims at: preventing the occurence of mobility limitation, reestablishing the muscular and neuromuscular balance, stimulating the normal infant development. The study was carried out on a 2-month-old patient diagnosed with congenital torticollis. The intervention program consisted in relaxing and stimulating massage, stretching, posture and facilitating exercises in accordance with the stages of development. Following the results, the initial hypothesis was confirmed, physical therapy managing to eliminate torticollis and facilitate normal neurological development of the infant.